Finance, Advertising, and Race - Célérier, Claire; Tak, Purnoor (Review of Financial Studies, 2025)
Abstract We study how bank advertising practices contribute to racial disparities in financial markets by steering minorities toward inferior products. We exploit a regulatory change that incentivizes deposit collection at the Freedman’s Savings Bank, the first institution to collect deposits from African Americans post-Emancipation, by facilitating misuse of depositor funds. After deregulation, advertising volume rises, particularly in African American newspapers, leading to increased deposits from Black depositors despite the bank’s insolvency. We identify persuasion as a key mechanism; prescriptive stereotypes and false claims likely amplify advertising’s impact on African Americans, exacerbating historically large depositor losses after the bank’s collapse.